Adaption of Synechococcus sp. IU 625 to growth in the presence of mercuric chloride - Chu, Tin-Chun (2011)
Resistance to heavy metals is important for the survival of bacteria in contaminated environments. In this study, we show that the unicellular cyanobacterial species Synechococcus sp. IU 625 adapts to growth in the presence of mercuric chloride, recovering from pigmentation and morphological defects. Cells accumulate mercury within two hours of growth and by three days, the total mercury concentration is significantly reduced, with all remaining mercury associated with the cells. This suggests that Synechococcus sp. IU 625 can convert mercury to a volatile form.